2018
DOI: 10.1525/mp.2018.36.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Links Between Speech Perception in Noise, Singing, and Cortical Processing of Music in Children with Cochlear Implants

Abstract: The perception of speech in noise is challenging for children with cochlear implants (CIs). Singing and musical instrument playing have been associated with improved auditory skills in normal-hearing (NH) children. Therefore, we assessed how children with CIs who sing informally develop in the perception of speech in noise compared to those who do not. We also sought evidence of links of speech perception in noise with MMN and P3a brain responses to musical sounds and studied effects of age and changes over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
0
10

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 93 publications
(88 reference statements)
9
51
0
10
Order By: Relevance
“…also sang to the infant. This suggests that parental singing is an inherent part of a child’s upbringing, which is important given research indicating that more parental singing potentially benefits not only parent–child bonding, but also encourages children to sing and is associated with better attention, speech perception in noise and language skills (Torppa et al, 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…also sang to the infant. This suggests that parental singing is an inherent part of a child’s upbringing, which is important given research indicating that more parental singing potentially benefits not only parent–child bonding, but also encourages children to sing and is associated with better attention, speech perception in noise and language skills (Torppa et al, 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A widely reported yet controversial benefit of music engagement is the so-called “musician advantage” in speech-in-noise (SIN) processing (for review, see Coffey et al, 2017 ). Several studies demonstrate that musicians outperform non-musicians in figure-ground perception, as measured in a variety of degraded speech recognition tasks ( Bidelman and Krishnan, 2010 ; Parbery-Clark et al, 2011 ; Swaminathan et al, 2015 ; Anaya et al, 2016 ; Clayton et al, 2016 ; Brown et al, 2017 ; Deroche et al, 2017 ; Du and Zatorre, 2017 ; Mankel and Bidelman, 2018 ; Torppa et al, 2018 ; Yoo and Bidelman, 2019 ). Amateur musicians (∼10 years training) are better at identifying and discriminating target speech amidst acoustic interferences including reverberation ( Bidelman and Krishnan, 2010 ) and noise babble ( Parbery-Clark et al, 2009a ).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the increasing amount of research findings in favor of the beneficial impact of music training on pitch-related performance in speech and music in CI users (J. K.-C. Chen et al, 2010; Fu et al, 2015; Gfeller et al, 1998; Torppa et al, 2014; Torppa, Faulkner, Kujala, Huotilainen, & Lipsanen, 2018), the underlying mechanisms accounting for the performance gain remains unclear. With the advent of modern brain imaging technologies, more and more evidence has been reported to show experience-related plasticity in the human brain (Green & Bavelier, 2008; Kempermann et al, 2010; Limb, Molloy, Jiradejvong, & Braun, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Because no perceptual data from the choir members with CIs were available in this study, it is unknown whether their superb vocal singing ability that resulted from the intensive music training would translate into better music perception, pitch perception, tone perception, speech perception, and eventually academic performance, and vice versa. Torppa et al (2018) recently reported that children with CIs with regular informal singing at home outperformed children with CIs with no singing activity in speech-in-noise perception tasks. It is conceivable that intensive formal music training might also enhance the perceptual performance and other aspects of speech-language abilities in children with CIs.…”
Section: Discussionmentioning
confidence: 99%